Diversity of Gastropods in The Mangrove Forest Area of Ujung Kulon National Park - Widyasari, Siti Fauziah; Wahyuni, Indria; Usman, Usman (BERKALA SAINSTEK, 2024)
Various kinds of reseources in coastal areas are very important for us to maintain sustainability. We can find coastal area with varios kinds of ecosystems in Ujung Kulon National Park. This study aims to determine the diversity of gastropods in the mangrove forest area of Ujung Kulon National Park. Sampling used the line transect method and the purposive sampling method with low tide conditions. Sampling was carried out at three stations which are divided into three transects at each station. The transect line was drawn along 50 m with each transect made 5 plots with a size 1 x 1 m2 with a distance between plots of 10 m. This research was held in May-June 2021. The data analysis includes the index values of diversity, dominance, evenness, and abundance. The results of the gastropod obtained consist of 20 species from 7 different families so that diversity index value were included in the medium category with the highest diversity index value owned by station 1 with a diversity index value of 2,03 and the lowest diversity index value owned by station 3 with a value of 1,56. The gastropod abundance index value has an average value of 273 ind/m2.